2009
DOI: 10.1007/s11325-009-0286-y
|View full text |Cite
|
Sign up to set email alerts
|

Austrian Moderate Altitude Studies (AMAS): benefits of exposure to moderate altitudes (1,500–2,500 m)

Abstract: Active vacations at moderate altitude are associated with a variety of positive health effects in persons with metabolic syndrome and in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…Furthermore, 5-10 days of adaptation to hypoxia returns hyperglycemia to basal levels in healthy people (5). Moreover chronic hypoxic exposure reduces fasting insulin and improves insulin resistance in type 2 diabetic patients (44)(45)(46) and decreases the insulin dosage in type 1 diabetic patients (47,48). Of note, lower insulin levels or reduced insulin signaling is beneficial for health and longevity (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5-10 days of adaptation to hypoxia returns hyperglycemia to basal levels in healthy people (5). Moreover chronic hypoxic exposure reduces fasting insulin and improves insulin resistance in type 2 diabetic patients (44)(45)(46) and decreases the insulin dosage in type 1 diabetic patients (47,48). Of note, lower insulin levels or reduced insulin signaling is beneficial for health and longevity (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…In a population-based study, it was shown that obesity risk was five times higher for those living at altitudes < 500 m above sea level as compared to residents of > 3000 m altitude (Voss et al, 2013). Recent studies demonstrated that high-altitude environment could be used in treatment of obesity (Schobersberger et al, 2010;Urdampilleta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a healthy individual undergoing a trek in the Himalayas at a mean altitude of 3900 m we described a significant increase in the number and clonogenic activity of EPCs one day after the trek, returning to normal after 45 days at sea level (Ciulla et al, 2005). A recent study conducted on healthy volunteers participating in a one-week hiking program on the Austrian Alps at 1700 m reported an increase in circulating EPCs (Schobersberger et al, 2010). It must however be remarked that in the case of these high-and moderate-altitude studies it is not possible to dissociate the effects of hypoxia from those of physical activity which is also a powerful stimulus for EPC upregulation Laufs et al, 2004).…”
Section: Hypoxia: a Common Cause Of Cell Damagementioning
confidence: 77%